2006
DOI: 10.1186/1744-9081-2-39
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the vesicular monoamine transporter 1 (VMAT1) gene with schizophrenia in a Japanese population

Abstract: BackgroundVesicular monoamine transporters (VMATs) mediate accumulation of monoamines such as serotonin, dopamine, adrenaline, and noradrenaline from the cytoplasm into storage organelles. The VMAT1 (alternatively solute carrier family 18: SLC18A1) regulates such biogenic amines in neuroendocrine systems. The VMAT1 gene maps to chromosome 8p21.3, a locus with strong evidence of linkage with schizophrenia. A recent study reported that a non-synonymous single nucleotide polymorphism (SNP) of the gene (Pro4Thr) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Given previous associations between Thr136Ile genotype and BPD 27 as well as both Thr4Pro and Ser98Thr genotypes with SZ 23 26 we used a translational research approach to investigate potential functional effects of these variants. Full length human VMAT1 cDNA is expressed in substantia nigra and was cloned for subsequent experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given previous associations between Thr136Ile genotype and BPD 27 as well as both Thr4Pro and Ser98Thr genotypes with SZ 23 26 we used a translational research approach to investigate potential functional effects of these variants. Full length human VMAT1 cDNA is expressed in substantia nigra and was cloned for subsequent experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we focus on VMAT1 which has recently emerged as a candidate gene for neuropsychiatric disorders. Several reports have shown that common missense variants in VMAT1 are associated with bipolar disorder (BPD), schizophrenia (SZ), anxiety-related personality traits and cognitive phenotypes related to SZ 23 29 . This is remarkable since the VMAT1 gene is located on chromosome 8p, a region previously implicated as a shared genomic susceptibility region for SZ/BPD in linkage scans.…”
Section: Introductionmentioning
confidence: 99%
“…SLC18A1 is mapped to chromosome 8p21.3, a locus with strong evidence for linkage with SZ 22 23 . SLC18A1 has been reported to be associated with SZ 24 25 26 27 . In this study, we detected an increased level of expression of SLC18A1 in SZ patients, providing further support for its possible involvement into SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Slc18a1 in mice reduces hippocampal neurogenesis and produces neurocognitive deficits [26]. Furthermore mutations in the Slc18a1 gene also have been linked to an increased likelihood of developing schizophrenia [33] and type 1 bipolar disease [20]. The decreased expression of this gene in the Large Suppressor group may reflect blunted synaptic plasticity in the nucleus accumbens; a difference which could contribute to the addiction phenotype.…”
Section: Discussionmentioning
confidence: 99%